Complications after systematic, random, and image-guided prostate biopsy - Borghesi,M; Ahmed,H; Nam,R; Schaeffer,E; Schiavina,R; Taneja,S; Weidner,W; Loeb,S (European Urology, 2016)
ContextProstate biopsy (PB) represents the gold standard method to confirm the presence of cancer. In addition to traditional random or systematic approaches, a magnetic resonance imaging (MRI)–guided technique has been introduced recently.ObjectiveTo perform a systematic review of complications after transrectal ultrasound (TRUS)–guided, transperineal, and MRI-guided PB.Evidence acquisitionWe performed a systematic literature search of Web of Science, Embase, and Scopus databases up to October 2015, according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Complications and mortality following random, systematic, and image-guided PBs were reviewed. Eighty-five references were included.Evidence synthesisThe most frequent complication after PB was minor and self-limiting bleeding (hematuria and hematospermia), regardless of the biopsy approach. Occurrence of rectal bleeding was comparable for traditional TRUS-guided and image-guided PBs. Almost 25% of patients experienced lower urinary tract symptoms, but only a few had urinary retention, with higher rates after a transperineal approach. Temporary erectile dysfunction was not negligible, with a return to baseline after 1–6 mo. The incidence of infective complications is increasing, with higher rates among men with medical comorbidities and older age. Transperineal and in-bore MRI–targeted biopsy may reduce the risk of severe infectious complications. Mortality after PB is uncommon, regardless of biopsy technique.ConclusionsComplications after PB are frequent but often self-limiting. The incidence of hospitalization due to severe infections is continuously increasing. The patient's general health status, risk factors, and likelihood of antimicrobial resistance should be carefully appraised before scheduling a PB.